RANCANG BANGUN MIKROSKOP RISET STEREO UNTUK MENDOKUMENTASIKAN VIDEO PERGERAKAN HYDRA SP SEBAGAI DAYA DUKUNG TERHADAP PRAKTIKUM SISTEMATIKA HEWAN AVERTEBRATA - Sutriyono Sutriyono (Integrated Lab Journal, 2018)
Research design research stereo microscope for video documenting the movement of Hydra sp as the carrying capacity of the practicum systematic invertebrate animals has been completed. This research was conducted at the Laboratory of Biology, Faculty of Science and Technology UIN Sunan Kalijaga. The purpose of this research is to document the movement picture and video of Hydra sp in practicum systematic invertebrate animals. Coupling research microscope with a digital camera that can save the video file is done through several stages of which is to connect a computer or laptop with a stereo microscope with a digital camera. The analysis used is descriptive analysis. The results of this research is a movement of Hydra sp video file that can be used as a medium of learning in a practical systematics invertebrates. In this study it can be concluded that the merger of the computer or laptop and stereo microscope with a digital camera can be used for video documenting the movement of Hydra sp.